PERSEPSI KONSUMEN PEREMPUAN PADA RISIKO PEMBELIAN (IMPLIKASI PENERAPAN STRATEGI BERSAING PRIVATE LABEL PADA GIANT HYPERMARKET PEKANBARU) - Antonius Manalu; Sri Zuliarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of research is how to women’s consumer perception at risk of purchasing in private label product Giant Hypermarket Pekanbaru. Private label is a brand created by companies in the retail and only get on the retail to low price. The perception of risk purchase is perceived as consumer on their results of decisions. The perception of risk purchase consists of six dimensions is functional risk, physical risk, financial risk, social risk, psychological risk and time risk. In the research of population is women’s consumer at Giant Hypermarket Pekanbaru. The technique of sampling is purposive sampling using Cochran’s formula, so that it can be 96 respondents. The research concludes that the perceptions of women’s consumer at risk of purchasing private label product of low category at Giant Hypermarket Pekanbaru.Keyword: women’s consumer, competitive strategy private label, risk of purchasing